Prophylactic Laser Treatment Posterior to Pars Plana Vitrectomy Sclerotomy Wounds during Macular Surgery: Laser Posterior to Sclerotomy Wounds - Ajlan, Radwan; Pfannenstiel, Matthew; Luvisi, Joseph (Kansas Journal of Medicine, 2022)
Introduction. Sclerotomy related retinal breaks (SRRBs) are a risk factor for postoperative Retinal detachment (RD). Endolaser posterior to sclerotomy wounds decreased the risk of SRRBs after 20G pars plana vitrectomy (PPV) for macular disease. However, similar data does not exist for 25G and 23G wounds.Methods. Retrospective cohort study of patients after 23G and 25G PPV for macular pathology between August 2017 and August 2020. The primary outcome was the postoperative rate of SRRBs or RDs. The secondary outcome was the postoperative rate of pupillary dysfunction and neurotrophic keratopathy. All participants had a minimum postoperative follow up of one year.Results. 117 patients were included in the study (62 in the laser group, and 55 in the control group). Mean age was 65.4±11.3 years (56.4% female and 43.6% male). Most of the laser group underwent 23G PPV (90%) while most of the control group underwent 25G PPV (96%). One patient in the control group developed RD secondary to a SRRB. No SRRBs or RDs developed in the laser group. None of the secondary outcomes developed in either group after one year.Conclusions. To the best of our knowledge, this is the first report in the literature on prophylactic laser posterior to small gauge sclerotomies (25G and 23G) during macular surgery. Laser treatment posterior to small gauge sclerotomies (25G and 23G) had a similar incidence of SRRBs as with 20G sclerotomies. Larger prospective studies are needed to further understand the role of laser in lowering SRRB risk.